Rituximab in combination with CNOP chemotherapy in patients withn previously untreated indolent non-Hodgkin's lymphoma - Economopoulos, T.; Fountzilas, G.; N. Pavlidis; Kalantzis, D.; Papageorgiou, E.; Christodoulou, C.; Hamilos, G.; Nicolaides, C.; Dimopoulos, M. (Hematology Journal, 2003)
Rituximab, a chimeric monoclonal antibody, produces response rates of up to 73% in patients with previously untreated indolent non-Hodgkin's lymphoma (NHL), and has high activity when combined with chemotherapy. The purpose of this phase II study was to determine the efficacy and safety of rituximab plus cyclophosphamide, mitoxantrone, vincristine and prednisone (CNOP) chemotherapy in patients with indolent NHL. In all, 42 patients (median age 67 years) with previously untreated follicular, marginal zone or small lymphocytic/lymphoplasmacytic NHL received six infusions of rituximab (375 mg/m2) in combination with six cycles of CNOP. The overall response rate was 90% comprising 30 complete (71%) and eight partial (19%) responses. Although patients with marginal zone lymphoma or International Prognostic Index (IPI) score 3 had lower complete response rates, no significant difference in overall response rate was observed between the histological groups (P = 0.24) or between patients stratified according to IPI score (P>0.05). Median overall survival, time-to-progression and response duration had not been reached after a median 19.5-month follow-up. In all, 31 patients (74%) are currently free from progression and 38 (90%) remain alive. Treatment was well tolerated. One patient (2% experienced grade 3/4 infusion-related toxicity; 13 (31%) grade 3/4 leukopenia and 18 (43%) grade 3/4 neutropenia. Infection was observed in nine patients: eight (19%) grade 1/2 and one (2.4%) grade 3. This study demonstrates that combining rituximab with CNOP achieves high remission rates without significant additional toxicity in patients with previously untreated indolent NHL. Further follow-up will determine response duration and survival.
Keywords: CNOP; Indolent NHL; rituximab